Doing visual analysis : from theory to practice - Ledin, Per, ....-; Machin, David, 1966- (Thousand Oaks, Calif. : Sage Publications, 2018)
Visual communication shapes our perceptions and experiences of the world. This is not only a question of photographs or video, but also the design of websites, the use of data visualization software, the branding of packaging, and even the design of buildings and furniture. Doing Visual Analysis: From Theory to Practices provides a concrete set of tools to research and analyse this wide range of visual data. Showing students how to apply the right mix of methods to their own research projects, it equips them with the skills to break down and analyse the range of contemporary visual communication. The book: Provides examples of how and where certain tools can be used in a project or dissertationDiscusses the type of research questions best suited to different tools and methodsShows students how to mix approaches and use tools alongside other methods, such as content analysis or interviews Doing Visual Analysis is an essential companion for students and researchers of visual data across the social sciences.